Quantitative perfusion assessment of gastric conduit with indocyanine green dye to predict anastomotic leak after esophagectomy. Issue 5 (16th December 2021) - Ishikawa, Yoshitaka; Breuler, Christopher; Chang, Andrew C; Lin, Jules; Orringer, Mark B; Lynch, William R; Lagisetty, Kiran H; Wakeam, Elliot; Reddy, Rishindra M
Summary: Impaired gastric conduit perfusion is a risk factor for anastomotic leak after esophagectomy. The aim of this study is to evaluate the feasibility of intraoperative quantitative assessment of gastric conduit perfusion with indocyanine green fluorescence angiography as a predictor for cervical esophagogastric anastomotic leak after esophagectomy. Indocyanine green fluorescence angiography using the SPY Elite system was performed in patients undergoing a transhiatal or McKeown esophagectomy from July 2015 through December 2020. Ingress (dye uptake) and Egress (dye exit) at two anatomic landmarks (the tip of a conduit and 5 cm from the tip) were assessed. The collected data in the leak group and no leak group were compared by univariate and multivariable analyses. Of 304 patients who were evaluated, 70 patients developed anastomotic leak (23.0%). There was no significant difference in patients' demographic between the groups. Ingress Index, which represents a proportion of blood inflow, at both the tip and 5 cm of the conduit was significantly lower in the leak group (17.9 vs. 25.4% [ P  = 0.011] and 35.9 vs. 44.6% [ P  = 0.019], respectively). Ingress Time, which represents an estimated time of blood inflow, at 5 cm of the conduit was significantly higher in the leak group (69.9 vs. 57.1 seconds, P  = 0.006). Multivariable analysis suggested that these three variables can be used to predict future leak. Variables of gastric conduit perfusion correlated with the incidence of cervical esophagogastric anastomotic leak. Intraoperative measurement of gastric conduit perfusion can be predictive for anastomotic leak following esophagectomy.